Restorative Treatment Patterns After Root Canal Obturation in Public Hospitals in Riyadh - AlSwayyed T; Bin Nafesah R; Alqutub M; Alfarhan A; Almashhaf A; Alshaikh H; Alhedeithi N (Dove Medical Press, 2021)
Tariq AlSwayyed,1,2 Raneem Bin Nafesah,2 Manal Alqutub,3 Ali Alfarhan,4 Arwa Almashhaf,5 Hessa Alshaikh,6 Nura Alhedeithi7 1College of dentistry, King Saud bin Abdulaziz University for Health Sciences, Riyadh, Saudi Arabia; 2Department of Dentistry, King Abdulaziz Medical City, Riyadh, Saudi Arabia; 3Princess Nourah Bint Abdulrahman University, Riyadh, Saudi Arabia; 4King Khalid University, Abha, Saudi Arabia; 5Ministry of Health, Riyadh, Saudi Arabia; 6King Saud bin Abdulaziz University for Health Sciences, Riyadh, Saudi Arabia; 7King Saud University, Riyadh, Saudi ArabiaCorrespondence: Raneem Bin NafesahKing Abdulaziz Medical City, Riyadh, Saudi ArabiaEmail ralnafisa@gmail.comAim: This study aims to describe the pattern of coronal restoration use among different dental specialties after root canal obturation in two governmental hospitals in Riyadh.Materials and Methods: Electronic dental records at King Abdul-Aziz Medical City and University Dental Hospital were reviewed. Teeth that underwent initial root canal treatment on a permanent tooth for obturation using gutta-percha between April 2019 and June 2019 were included. The collected data included the type of material used for coronal restoration after RCT, immediate post-space preparation, cotton pellet placement, the clinical title and specialty of the treating physician, and the center where treatment was performed. Excel was used for data collection. IBM SPSS was used for descriptive and interferential analyses.Results: A total of 763 patients were included in the study, in which the double seal technique was used in 56% of the patients, followed by Cavit, which was used in approximately 17% of the patients. Post space was prepared immediately after root canal treatment in 49 patients, and only 17 teeth received the final post, whereas post space was temporized for the rest of the prepared teeth and received the final post at the following visits. Significant relations were found between the type of material used and the clinical title of the treating physician and between the material of choice and the specialty of the dentist. The double seal was the technique of choice among endodontists and restorative dentists, whereas advanced general dentists frequently used Cavit. The least used materials were IRM, amalgam, and Ketac Silver.Conclusion: The double seal technique was found to be the most commonly used method to achieve a coronal seal, followed by Cavit. Other materials used after RCT, in sequential order based on the frequency of use, were GIC, temporary crowns, resin composite, RMGIC, prefabricated post with composite buildup, IRM, amalgam, and Ketac Silver.Keywords: coronal restoration, temporary fillings, endodontic treatment, restorative treatment, root canal treatment